Valorization of pulp and paper industry wastewater using sludge enriched with nitrogen‐fixing bacteria. (29th June 2021) - Ospina‐Betancourth, Carolina; Acharya, Kishor; Allen, Ben; Head, Ian M.; Sanabria, Janeth; Curtis, Thomas P.
Abstract: Nitrogen‐fixing bacteria (NFB) can reduce nitrogen at ambient pressure and temperature. In this study, we treated effluent from a paper mill in sequencing batch reactors (SBRs) and monitored the abundance and activity of NFB with a view to producing a sludge that could work as a biofertilizer. Four reactors were inoculated with activated sludge enriched with NFB and fed with a high C/N waste (100:0.5) from a paper mill. Though the reactors were able to reduce the organic load of the wastewater by up to 89%, they did not have any nitrogen‐fixing activity and showed a decrease in the putative number of NFB (quantified with qPCR). The most abundant species in the reactors treating high C/N paper mill wastewater was identified by Illumina MiSeq 16S rRNA gene amplicon sequencing as Methyloversatilis sp. (relative abundance of 4.4%). Nitrogen fixation was observed when the C/N ratio was increased by adding sucrose. We suspect that real‐world biological nitrogen fixation (BNF) will only occur where there is a C/N ratio ≤100:0.07. Consequently, operators should actively avoid adding or allowing nitrogen in the waste streams if they wish to valorize their sludge and reduce running costs. Practitioner points: Efficient biological wastewater treatment of low nitrogen paper mill effluent was achieved without nutrient supplementation. The sludge was still capable of fixing nitrogen although this process was not observed in the wastewater treatment system. This high C/N wastewater treatment technology could be used with effluents from cassava flour, olive oil, wine and dairy industries. Abstract : This low‐nitrogen wastewater treatment system, inoculated with a mixed microbial culture, has potential as a source of nitrogen‐fixing bacteria that could be used as a biofertiliser.